Mediating effect of communication power on the relationships between networking and career success: a structural equation modeling approach - Wok, Saodah; Hashim, Junaidah (IBIMA Publishing, 2017)
This study aims to investigate the mediating effect of communication power on the relationships between mentoring and career success. It also tests the moderating effects of proactive personality and self-efficacy in the model. The study employs a quantitative research design, using survey method with questionnaire as the instrument for data collection.The population of interest is the employees at the supervisory or managerial position in various organizations in Malaysia. A sample size of 400 supervisor/managers was used for the study. Most of the measures were adapted from established scales. The findings reveal that there is a mediating effect of communication power on the relationships. This means that mentoring influences the communication power which in turn influences career success. This study makes a significant contribution to the existing knowledge because not much is known about the effect of communication power on career success except for the work of Castells (2007). With the present influence of communication technology at the workplace, the findings of this study are useful to Human Resource (HR) practitioners for strategizing organisation career management and mentoring programme. This study does not only examine the effect of the two variables, information power and career success; it goes a step further by taking mentoring into the model.